Praktik Knowledge Sharing Dari Perspektif Organisasi Mahasiswa Pada Politeknik Negeri Pontianak - Lilis Listiyawati; Riska Wahyuni; Anggita Anggita (Departement of Mathematics Education, 2023)
The Association of Business Administration Students (HMJ AB) at Polnep is an independent organization with autonomy within the scope of the Business Administration Department. In accordance with the HMJ AB Articles of Association, the functions of this student organization are, first, to serve as a platform for students in the Business Administration department to express their aspirations, interests, talents, and abilities. The second function is to develop the academic and practical works of students in the Business Administration department, share knowledge, shape mentality, and foster organizational attitudes and behaviours both within and outside the organization. Recognizing the importance of one of HMJ AB's functions in the aspect of knowledge sharing, this research is conducted because HMJ AB is an intra-campus organization, and Polnep has an interest in helping optimize this function to enhance the quality of graduates in line with the institution's vision and mission. This research is conducted at the State Polytechnic of Pontianak on HMJ AB, focusing on the practice of knowledge sharing (KS) from the perspective of the student organization. The objectives of this research are to know the practice of knowledge sharing in HMJ AB, identify the types of information commonly shared, explore the challenges in the practice of knowledge sharing in HMJ AB and solutions to overcome these challenges. This is a qualitative research study using a descriptive method. The data sources for this research are students affiliated with HMJ AB, the organization's executives, and HMJ advisors during the term of HMJ AB for the 2022-2023 period. Data collection is conducted through interviews and documentary studies. The research results indicate that knowledge sharing is already implemented, but the execution is not yet optimal, considering the number of KS activities conducted during the HMJ period, materials that are not tailored to the members' needs, and low attendance of members. The shared knowledge relates to government seminars, entrepreneurship seminars, coffee barista training, and social activities during Ramadan. Challenges include low member motivation, lacking soft skills, insufficient communication skills, and a lack of involvement from the department and lecturers in supporting KS activities. Proposed solutions from the respondents include discussions where members are involved in determining priority KS information to be shared, providing rewards, and enhancing communication between HMJ and internal or external parties.